Comparison of stereotactic brain biopsy techniques in dogs: neuronavigation, 3D-printed guides, and neuronavigation with 3D-printed guides - Shinn, Richard L.; Hollingsworth, Christopher; Parker, Rell L.; Rossmeisl, John H.; Werre, Stephen R. (Frontiers in Veterinary Science, 2024)
The objective of this research was to compare two previously described stereotactic brain biopsy (SBB) techniques, three-dimensional skull contoured guides (3D-SCGs) and neuronavigation with Brainsight, to a novel SBB technique using Brainsight combined with a 3D-printed headframe (BS3D-HF) to improve the workflow of SBB in dogs. This was a prospective methods comparison with five canine cadavers of different breeds and size. Initial helical CT was performed on cadavers with fiducial markers in place. Ten different target points were randomly selected for each method. The headframe for the BS3D-HF was designed and printed. Trajectories were planned for each method. Steinmann pins (SPs) were placed into the target points using the planned trajectories for each method, and CT was repeated (post CT). Accuracy was assessed by overlaying the initial CT onto the post CT and measuring the difference of the planned target point to the SP placement. For 3D-SCG, the median deviation was 2.48mm (0.64-4.04). With neuronavigation, the median deviation was 3.28mm (1.04-4.64). For BS3D-HF, the median deviation was 14.8mm (8.87-22.1). There was no significant difference between 3D-SCG and neuronavigation for the median deviation (p=.42). When comparing BS3D-HF to 3D-SCG, there was a significant difference in the median deviation (p<.0001). Additionally, when comparing BS3D-HF to neuronavigation, there was a significant difference for the median deviation (p<.0001). Our findings concluded that both 3D-SCGs and neuronavigation were accurate for SBB, however BS3D-HF was not. Although feasible, the current BS3D-HF technique requires further refinement before it can be recommended for use for SBB in dogs.